Utilization of Moringa oleifera as Natural Coagulant for Water Purification - Ng, Meng Hong; Elshikh, Mohamed Soliman (Industrial and Domestic Waste Management, 2021)
The plant-based natural coagulant has the potential to substitute the chemical coagulant in the water treatment process. In this work, the potential of plant-based natural coagulants in the ability of turbidity removal was identified. The Moringa oleifera seed was selected for the batch analysis test such as pH, contact time, agitation, and dosage. The high alkaline water decreases the effectiveness of plant-based natural coagulants. The agitation and contact time show the importance of the coagulation process. The optimum turbidity removal rate in pH is 4, the contact time is 60 seconds and 3000 seconds for coagulation and flocculation, respectively, the agitation is 300 RPM and 30 RPM for coagulation and flocculation, and lastly, the dosage is 10 g of Moringa oleifera seed. Finally, the plant-based natural coagulants demonstrated the ability to remove turbidity and could be used in place of chemical coagulants.